Virus‐induced gene silencing in transgenic plants: transgene silencing and reactivation associate with two patterns of transgene body methylation. (12th July 2014) - Zhao, Mingmin; San León, David; Delgadillo, Ma. Otilia; García, Juan Antonio; Simón‐Mateo, Carmen
Summary We used bisulfite sequencing to study the methylation of a viral transgene whose expression was silenced upon plum pox virus infection of the transgenic plant and its subsequent recovery as a consequence of so‐called virus‐induced gene silencing (VIGS). VIGS was associated with a general increase in the accumulation of small RNAs corresponding to the coding region of the viral transgene. After VIGS, the transgene promoter was not methylated and the coding region showed uneven methylation, with the 5′ end being mostly unmethylated in the recovered tissue or mainly methylated at CG sites in regenerated silenced plants. The methylation increased towards the 3′ end, which showed dense methylation in all three contexts (CG, CHG and CHH). This methylation pattern and the corresponding silenced status were maintained after plant regeneration from recovered silenced tissue and did not spread into the promoter region, but were not inherited in the sexual offspring. Instead, a new pattern of methylation was observed in the progeny plants consisting of disappearance of the CHH methylation, similar CHG methylation at the 3′ end, and an overall increase in CG methylation in the 5′ end. The latter epigenetic state was inherited over several generations and did not correlate with transgene silencing and hence virus resistance. These results suggest that the widespread CG methylation pattern found in body gene bodies located in euchromatic regions of plant genomes may reflect an older silencing event, and most likely these genes are no longer silenced.